The defense of community in Peru's central highlands : peasant struggle and capitalist transition, 1860-1940 - Mallon, Florencia E., 1951- (Princeton legacy library, 1983)
Florencia E. Mallon examines the development of capitalism in Peru's central highlands, depicting its impact on peasant village economy and society. She shows that the region's peasantry divided into an agrarian bourgeoisie and a rural proletariat during the period under discussion, although the surviving peasant ideology, village kinship networks, and the communality inspired by economic insecurity have sometimes obscured this division. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.